Note from the editor: Taxing inequality and fiscal sociology - Ákos Róna-Tas (economic sociology_the european electronic newsletter, 2020)
In recent years, fiscal sociology has grown to become one of the most vibrant subfields in economic sociology. For a long time, its core topic - public finance - was considered to lie beyond the discipline of sociology, despite the contributions of Rudolph Goldscheid, Fritz Karl Mann, and Joseph Schumpeter, the founders of fiscal sociology over a century ago, who established that there is an essential connection between state finances and the wider social order. New fiscal sociology is reclaiming this connection at a time when the role of the state in the economy is becoming increasingly pronounced and visible.
Keywords: 300